Advertising Gamification as an Educational Tool: A Quantitative Study in University Training Environments - Larraga, Liliana Coronado; Navarro, Juan Jose Lopez; Vilema, Manuel David Isin; Fonseca, Diana Marcela Figueroa; Torrecillas, Diego Omar Guevara (Journal of Posthumanism, 2025)
Gamification has been presented as a revolutionary tactic to promote learning in training contexts. This quantitative analysis examines the effect of advertising gamification as a teaching resource in university environments, assessing its effectiveness in motivating, preserving knowledge and involving students. A structured survey was carried out with 210 students from universities in Latin America, followed by a descriptive and inferential statistical study. The findings indicate that gamification based on advertising actions significantly enhances motivation and enhances content comprehension, establishing itself as an effective pedagogical option. It is recommended that it be systematically incorporated into higher education programmes.